A First Look at Mobile-Live-Users of a Large CDN - Silva, Daniel Vasconcelos Correa da; Rocha, Antônio A. de A.; Velloso, Pedro B.; Domingues, Guilherme de Melo Baptista (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
Video streaming is one of the greatest application on the Internet, and mobile devices became more powerful and popular every passing day. Understanding live-streaming-mobile-user behavior is imperative to map issues, to then seek solutions. The purpose of this work is to characterized mobile users watching popular live events, such as Dilma’s Impeachment and Opening of Rio2016 Games.